2013
DOI: 10.1089/ars.2013.5246
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding Success and Failures in the Use of Selenium for Cancer Prevention

Abstract: Significance: Adequate and supranutritional selenium (Se) intake, maintaining full expression of selenoproteins, has been assumed to be beneficial for human health with respect to prevention of cancer. Strikingly, the effectiveness of dietary Se supplementation depends on many factors: baseline Se status, age, gender, and genetic background of an individual; type of cancer; and time point of intervention in addition to metabolic conversion and dose of applied Se compounds. Recent Advances: Se intake levels for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 92 publications
(132 reference statements)
1
51
0
5
Order By: Relevance
“…This is particularly relevant to better understand the role of Se in the prevention and progression of certain diseases (e.g., prostate cancer and type 2 diabetes), which has become unclear after publication of diverging results from large-scale Se intervention trials. 18,[84][85][86] Another research priority is to gain more insight into the inhibition of DNMT and HDAC enzymes by Se, to identify the active Se species, their possible DNMT/HDAC isoform specificity, mechanism of inhibition and the required doses for inhibition in vitro and in vivo. Se-responsive signaling pathways that influence nuclear proteins linked to epigenetic mechanisms, e.g., through nucleosomal remodeling, transcription or DNA repair, as exemplified for GADD45A, also need to be examined closer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly relevant to better understand the role of Se in the prevention and progression of certain diseases (e.g., prostate cancer and type 2 diabetes), which has become unclear after publication of diverging results from large-scale Se intervention trials. 18,[84][85][86] Another research priority is to gain more insight into the inhibition of DNMT and HDAC enzymes by Se, to identify the active Se species, their possible DNMT/HDAC isoform specificity, mechanism of inhibition and the required doses for inhibition in vitro and in vivo. Se-responsive signaling pathways that influence nuclear proteins linked to epigenetic mechanisms, e.g., through nucleosomal remodeling, transcription or DNA repair, as exemplified for GADD45A, also need to be examined closer.…”
Section: Discussionmentioning
confidence: 99%
“…36 VHL is frequently downregulated and mutated in renal cell carcinomas and also found to be deregulated during colorectal carcinogenesis, 37 wherein Se has been attributed protective functions based on epidemiological and animal studies. 18,38 A study with humans assessed the methylation status of colorectal cancer-related genes in healthy rectal mucosa specimens (84 males, 101 females) in relation to Se status. 39 An association was found for WIF1 (wnt inhibitory factor 1) methylation and plasma Se concentration.…”
Section: Influence Of Selenium On Epigenetic Modifications Of Dna Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It has chemopreventive, anti-inflammatory, antiviral properties and is related in enhancing immunity (Rayman, 2012;Steinbrenner et al, 2013). The health-related properties of Se include but are not limited to protection against cancer, proper function of thyroid gland, and protection against cardiovascular and muscle disorders (Mao and Teng, 2013;Rocourt and Cheng, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Three articles in this Forum (Bode and Dong, Kim et al, Wilking et al) have discussed several important well-known as well as some emerging potential targets based on redox signaling and interactions (1,3,8). The other five articles (Khan et al, Li et al, Park and Pezzuto, Steinbrenner et al, Yum et al) have discussed known and emerging antioxidants that may be useful in the prevention as well as treatment of cancer (2,4,5,7,9).In the first original research communications article on pages 89-101 of this Forum (3), Kim and colleagues investigated a new interacting protein partner of NFE2-related factor 2 (Nrf2), which is a transcription factor that controls and integrates stress signals in mammalian cells and responds by modulating a variety of transcriptional programs. Employing the one-strep tag pull-down and LTQ Orbitrap liquid chromatographytandem mass spectrometry, Kim et al identified IQ motif containing GTPase activating protein 1 (IQGAP1) as a new Nrf2 interacting partner.…”
mentioning
confidence: 99%